Epigenetics and autoimmune diseases: the X chromosome-nucleolus nexus - Brooks, Wesley H.; Renaudineau, Yves (Frontiers in Genetics, 2015)
Autoimmune diseases occur more often in females, suggesting a key role for the X chromosome. X chromosome inactivation, a major epigenetic feature in female cells that provides dosage compensation of X-linked genes to avoid overexpression, presents special vulnerabilities that can contribute to the disease process. Disruption of X inactivation can result in loss of dosage compensation with expression from previously sequestered alleles, imbalance of gene products, and altered endogenous material out of normal epigenetic context. In addition, the human X has significant differences compared to other species and these differences can contribute to the frequency and intensity of the autoimmune disease in humans as well as the types of autoantigens encountered. Here a link is demonstrated between autoimmune diseases, such as systemic lupus erythematosus, and the X chromosome by discussing cases in which typically non-autoimmune disorders complicated with X chromosome abnormalities also present lupus-like symptoms. The discussion is then extended to the reported spatial and temporal associations of the inactive X chromosome with the nucleolus. When frequent episodes of cellular stress occur, the inactive X chromosome may be disrupted and inadvertently become involved in the nucleolar stress response. Development of autoantigens, many of which are at least transiently components of the nucleolus, are then described. Polyamines, which aid in nucleoprotein complex assembly in the nucleolus, increase further during cell stress, and appear to have an important role in the autoimmune disease process. Autoantigenic endogenous material can potentially be stabilized by polyamines. This presents a new paradigm for autoimmune diseases: that many are antigen-driven and the autoantigens originate from altered endogenous material due to cellular stress that disrupts epigenetic control. This suggests epigenetics and the X chromosome have important roles in autoimmune disorders.